2017
DOI: 10.1016/j.jssc.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-oxide-supported CuAl and CoAl layered double hydroxides as enhanced catalysts for carbon-carbon coupling via Ullmann reaction

Abstract: Two efficient catalyst based on CuAl and CoAl layered double hydroxides (LDHs) supported on graphene oxide (GO) for the carbon-carbon coupling (Classic Ullmann Homocoupling Reaction) are reported. The pure and hybrid materials were synthesised by direct precipitation of the LDH nanoparticles onto GO, followed by a chemical, structural and physical characterization by electron microscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA), surface area measurements, X-ray photoelectron spectroscopy (XPS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…This characteristics properties were found as similar as shown by research reported from Dong and co-workers [11]. Besides that, the SEM images of LDH nanofillers shows that the CuAl LDH particles cluster all together as shown in red circle in figure 2 c) into a large aggregates mainly caused by high surface charge and surface tension [11,13].…”
Section: Ldh Morphological Structuressupporting
confidence: 87%
“…This characteristics properties were found as similar as shown by research reported from Dong and co-workers [11]. Besides that, the SEM images of LDH nanofillers shows that the CuAl LDH particles cluster all together as shown in red circle in figure 2 c) into a large aggregates mainly caused by high surface charge and surface tension [11,13].…”
Section: Ldh Morphological Structuressupporting
confidence: 87%
“…This distortion is attributed to the Jahn‐Teller effect for Cu in an octahedral environment, which leads to long‐range disordering. It should be noted that the Cu 2 Al‐HTLCs hydrotalcite‐like compound shows an sharp and narrow diffraction peak, which exhibits identical pattern to that of the reference patterns for the Cu−Al hydrotalcite‐like compound (PDF 46–0099), suggesting that Cu 2 Al‐HTLCs hydrotalcite‐like precursor is also well prepared with the layered double hydrotalcite‐like‐type structure …”
Section: Resultsmentioning
confidence: 99%
“…These reections are the characteristics of LDH in like hydrotalcite phase. 27 The 33 The XPS spectrum of O 1s (Fig. 3d) shows a strong peak corresponding to the O-H bond of the carboxyl group on the SWCNT surface.…”
Section: Synthesis and Characterization Of Cual-ldh/swcnts Nanocompositementioning
confidence: 99%